DOI: 10.31274/rtd-180813-10409
|View full text |Cite
|
Sign up to set email alerts
|

Biology of seed transmission of Erwinia stewartii in maize

Abstract: This manuscript has been rqiroduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter fiice, ^^e others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Early reports suggested that seed transmission played an important role in the occurrence of Stewart's disease (24,30). However, recent studies by Michener et al (18), Block et al (2)(3)(4), and Khan et al (12) all have shown that the risk of seed-to-seedling transmission of P. stewartii is extremely low. In their study, Khan et al (12) grew 75,000 plants from seed that was harvested from P. stewartiiinfected plants and did not find any seedto-seedling transmission of P. stewartii in the test plants; however, they did not determine the actual percentage of P. stewartii-infected (or infested) seed.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Early reports suggested that seed transmission played an important role in the occurrence of Stewart's disease (24,30). However, recent studies by Michener et al (18), Block et al (2)(3)(4), and Khan et al (12) all have shown that the risk of seed-to-seedling transmission of P. stewartii is extremely low. In their study, Khan et al (12) grew 75,000 plants from seed that was harvested from P. stewartiiinfected plants and did not find any seedto-seedling transmission of P. stewartii in the test plants; however, they did not determine the actual percentage of P. stewartii-infected (or infested) seed.…”
mentioning
confidence: 83%
“…Isolate stability was confirmed by serial transfers onto nonselective media and by plant inoculation and re-isolation. No evidence of back mutation was observed (2). Prior to inoculation, cultures were incubated for 48 h at 25ºC on nutrient broth yeast extract agar (NBY) amended with cycloheximide (100 µg/ml), rifampicin (50 µg/ml), and nalidixic acid (40 µg/ml (NBY-CRN).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then in 1962 based on the similarity of its physical properties. Pathogenic bacteria changed their name to Erwinia stewartii (Smith) (Lamka, 1990;Block, 1996;Cushatt, 2020). Some of these name changes were made based on the morphological and physiological characteristics of the pathogen.…”
Section: History Development Of Taxonomy and Characteristicsmentioning
confidence: 99%